Syphilitic hepatitis - Łukasz Supronowicz; Magdalena Rogalska (Clinical & Experimental Hepatology)
Syphilis is a sexually transmitted multisystemic disease known as “the great imitator” due to its variable presentations. Despite being preventable and curable, it still constitutes a major health problem. Hepatic manifestation of syphilis is usually mild cholestatic liver injury but in very rare cases can become fulminant. Moreover, syphilitic hepatitis, known for several decades, is considered rare but is probably under-diagnosed. Given the significant morbidity associated with a missed diagnosis, syphilitic hepatitis should be taken into account as an element of differential diagnosis in patients with unexplained elevation of liver enzymes.